The Consequences of Copyright: The Origins and Implications of Architectural Copyright Protection and Its Impact on Originality in Design - (:unkn) unknown (My University, 2019)
The Architectural Works Copyright Protection Act was heralded as a major step forward in the protection of original design ideas. However, since its inception in 1990, a number of shortcomings that have reduced its effectiveness have become apparent. Most recently, a potentially major consequence of the act, unforeseen at its creation, has emerged, leading to considerable litigation that may have significant repercussions for design freedom, actually reducing or inhibiting the concept of originality in design. Its impacts on architecture, urbanism, and architectural education are still unknown. This paper explores the implications of copyright protection and limitations on design, examining the unforeseen shortcomings and negative consequences of its enforcement, and reviews several recent judicial decisions that suggest some positive modification in the interpretation of copyright protection. The paper concludes with an account of the impact of the act on originality within the architectural profession and suggests some strategies for architects to safeguard their intellectual property while maintaining control of their original ideas in the design process.